THE EFFECTIVENESS OF THE SUKABUMI REGENCY KPU ELECTION SMART HOUSE PROGRAM IN INCREASING POLITICAL PARTICIPATION - Mugia Resti Sinta Firdaus Daelani; Rizki Hegia Sampurna; Andi Mulyadi (DIA: Jurnal Administrasi Publik, 2024)
The General Election Commission is an election management body and has the task of providing political education to the public. One form of the government's efforts to increase political participation is by holding the Election Smart House program. (RPP). In line with that, the Sukabumi Regency KPU also runs the RPP program to educate the public about elections and democracy so that it is hoped that it can increase people's political participation. This study aims to analyze the effectiveness of the Sukabumi District KPU Election Smart House program in increasing political participation. This type of research is qualitative research. The theory used is the theory of effectiveness according to Duncan, the techniques used are observation, interviews and documentation. Based on the results of the research that has been done. In conclusion, based on the analysis results, the RPP program is quite effective in increasing the political participation of the people of Sukabumi Regency.